Impact of Community-Based Nutrition Interventions on Children with Undernutrition Aged 6-23 Months: A Systematic Literature Review - Rahayu Widaryanti; Martha Irene Kartasurya; Mohammad Zen Rahfiludin; Sri Achadi Nugraheni (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Providing optimal nutritional interventions during critical ages can save children from the risk of malnutrition and long-term health effects such as growth disorders, cognitive disorders, illness, and death. Although the WHO has issued guidelines for community-based nutritional interventions, their implementation varies across regions. To explore the impact of community-based nutrition interventions on children with undernutrition aged 6–23 months. Methods: This study used the reporting guidelines from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), which have been registered with PROSPERO with registration number CRD420251008033. The search strategy employed the Population-Intervention-Comparisons-Outcomes (PICO) framework. The search was conducted using databases from Scopus, PubMed, and ProQuest. Risk of bias assessment used the critical appraisal tool from the Joanna Briggs Institute (JBI). Results: 13 articles were reviewed in this systematic review, consisting of 9 RCTs and four quasi-experimental studies. Community-based nutrition interventions identified in the literature review included nutrition education for parents or caregivers of children with malnutrition, such as stunting, wasting, underweight, or anemia, aged 6–23 months. Other interventions included behavior change communication, complementary feeding practices, or food supplementation, as well as integrated community health programs and cash transfer and economic-support models. Conclusion: Community-based nutrition interventions, particularly nutrition education, can significantly improve mothers' knowledge and behavior in managing malnutrition. However, interventions will have a greater impact when combined with other interventions, such as behavior change communication, food supplementation, cash transfers, and integrated programs across various sectors. These findings can serve as a basis for policy formulation and implementing malnutrition prevention programs targeting vulnerable groups through targeted and sustainable community-based nutrition interventions.